Noise exposure of orchestra members measurement uncertainty related to sampling - RUDNO-RUDZIŃSKI, Krzysztof (Archives of Acoustics, 2007)
One of the objectives in workplace noise measurement and assessment practice is to minimize the costs of testing while ensuring that its purpose is achieved, i.e. it is determined if the permissible noise exposure level has not been exceeded. Time reduction results in increased measurement uncertainty whereby the risk that it will be necessary to repeat the tests increases.Noise exposure measurements were carried out in opera orchestra. The technique of equivalent noise level measurement in consecutive one-minute intervals, with full recording of results, was employed. Measurements were performed simultaneously on 8 workstations.The results of the measurements were subjected to a statistical analysis in order to determine the measurement uncertainty associated with performing the measurements by sampling in time intervals of different duration.